Effect of Two‐Year Caloric Restriction on Bone Metabolism and Bone Mineral Density in Non‐Obese Younger Adults: A Randomized Clinical Trial. (24th September 2015) - Villareal, Dennis T; Fontana, Luigi; Das, Sai Krupa; Redman, Leanne; Smith, Steven R; Saltzman, Edward; Bales, Connie; Rochon, James; Pieper, Carl; Huang, Megan; Lewis, Michael; Schwartz, Ann V; et al.
ABSTRACT: Although caloric restriction (CR) could delay biologic aging in humans, it is unclear if this would occur at the cost of significant bone loss. We evaluated the effect of prolonged CR on bone metabolism and bone mineral density (BMD) in healthy younger adults. Two‐hundred eighteen non‐obese (body mass index [BMI] 25.1 ± 1.7 kg/m 2 ), younger (age 37.9 ± 7.2 years) adults were randomly assigned to 25% CR (CR group, n = 143) or ad libitum (AL group, n = 75) for 2 years. Main outcomes were BMD and markers of bone turnover. Other outcomes included body composition, bone‐active hormones, nutrient intake, and physical activity. Body weight (–7.5 ± 0.4 versus 0.1 ± 0.5 kg), fat mass (–5.3 ± 0.3 versus 0.4 ± 0.4 kg), and fat‐free mass (–2.2 ± 0.2 versus –0.2 ± 0.2 kg) decreased in the CR group compared with AL (all between group p < 0.001). Compared with AL, the CR group had greater changes in BMD at 24 months: lumbar spine (–0.013 ± 0.003 versus 0.007 ± 0.004 g/cm 2 ; p < 0.001), total hip (–0.017 ± 0.002 versus 0.001 ± 0.003 g/cm 2 ; p < 0.001), and femoral neck (–0.015 ± 0.003 versus –0.005 ± 0.004 g/cm 2 ; p = 0.03). Changes in bone markers were greater at 12 months for C‐telopeptide (0.098 ± 0.012 versus 0.025 ± 0.015 μg/L; p < 0.001), tartrate‐resistant acid phosphatase (0.4 ± 0.1 versus 0.2 ± 0.1 U/L; p = 0.004), and bone‐specific alkaline phosphatase (BSAP) (–1.4 ± 0.4 versus –0.3 ± 0.5 U/L; p = 0.047) but not procollagen type 1 N‐propeptide; at 24 months, only BSAP differed between groups (–1.5 ± 0.4 versus 0.9 ± 0.6 U/L; p = 0.001). The CR group had larger increases in 25‐hydroxyvitamin D, cortisol, and adiponectin and decreases in leptin and insulin compared with AL. However, parathyroid hormone and IGF‐1 levels did not differ between groups. The CR group also had lower levels of physical activity. Multiple regression analyses revealed that body composition, hormones, nutrients, and physical activity changes explained ∼31% of the variance in BMD and bone marker changes in the CR group. Therefore, bone loss at clinically important sites of osteoporotic fractures represents a potential limitation of prolonged CR for extending life span. Further long‐term studies are needed to determine if CR‐induced bone loss in healthy adults contributes to fracture risk and if bone loss can be prevented with exercise. © 2015 American Society for Bone and Mineral Research.